Application of nursing skills competition in teaching of Surgical Nursing (护理技能竞赛在《外科护理学》教学中的应用研究) - FENG Lin (冯琳); LI Ping (李萍); LU Fang (卢放) (中西医结合护理)
Objective To evaluate the application of nursing skills competition in teaching of Surgical Nursing. Methods Totally 183 nursing students were divided into the observation group (n=93)and control group (n=90) by lottery method. Conventional teaching method was adopted in the control group, and the nursing skills competition combined with practical teaching was used in teaching of Surgical Nursing in the observation group. The teaching effect, student’s independent learning ability, problem analyzing-solving ability were measured and compared between two groups. Results Students in the observation group achieved higher scores of theoretical test and practice skills assessment compared with those in the control group (P＜0. 01). Higher level of independent learning ability and problem analyzing-solving ability were evaluated in the observation group than those in the control group (P＜0. 01). Conclusion Nursing skills competition is an effective approach of improving the quality of clinical teaching and training. (目的 探讨护理竞赛在《外科护理学》教学中的应用效果。方法 选取某医学院2019级护理专业学生共183名作为研究对象, 采取抽签法分为观察组(n=93)和对照组(n=90)。对照组采用常规教学方法, 观察组在对照组基础上增加护理技能竞赛并结合实践教学分析。对两组学生的教学效果、考试成绩、技能掌握情况进行比较。结果 研究组学生理论考核和技能操作实践考核成绩优于对照组, 差异有统计学意义(P＜0. 01); 观察组学生自主学习能力、分析和解决问题能力评价高于对照组, 差异有统计学意义(P＜0. 01)。结论 在《外科护理学》课程教学中融入护理技能竞赛, 能有效提高教学水平, 提升临床护理人才培养质量, 对改善教学效果具有重要作用。)